Transformation of Digital Libraries and Efforts to Increase Information Literacy - Hardi Wahono, Irva Yunita, Zahwa Tara Fadhila, (Jurnal El-Pustaka, 2024)
Digital libraries have transformed into gateways to boundless information. Physical book collections now exist in digital format, opening wider and more accessible avenues to knowledge. Their role goes beyond simply providing books, extending to enhancing the digital information. Users can now easily search for and evaluate information, develop critical thinking skills, understand online safety, and even embark on flexible, self-directed learning journeys. Digital libraries act as windows opening new opportunities in the digital age. However, gaps remain to be bridged, such as uneven internet access and suboptimal digital literacy levels. Collaboration among various stakeholders, including government, libraries, academics, and the public, is key to maximizing the potential of digital libraries and empowering communities in this information-rich era.